Piloting the G + Customer and Product Profile Tools for gender-responsive bean breeding in Zimbabwe - Nchanji, Eileen; Lutomia, Cosmas; Rubyogo, Jean-Claude; Chirwa, Rowland; Onyango, Patricia; Nyarai, Chisorochengwe; Tsekenedza, Shylet; Gutsa, Freeman; Lloyd, Sondayi (2022)
Gender is an integral part of bean breeding initiatives and provides the platform through which plant breeding should be implemented. Gender-sensitive breeding offers a clear focus on addressing gender gap in agriculture by considering different traits preferred by both men and women (Nchanji et al., 2021b). Through the gender lens, critical elements in women and men’s preferences are consulted even though such profiles do not necessarily have different traits for men and women (Nchanji et al., 2021b). Breeding teams are therefore capable of assessing gender-relevant differences in preferences, constraints, needs, and potential impact on women and men’s livelihood strategies. This observation is founded on the critical role women play in production of common beans in Zimbabwe. Therefore, their participation in bean breeding initiatives is considered essential because it is regarded as a women’s crop (PABRA 2015a). The CGIAR gender and breeding initiative has developed an important tool to guide breeders in identifying the gender gaps and preferences of customer to develop and prioritize new product that address persistent gender gaps in crop production. The tool; G+ product and customer profile recognizes changes in the modern agriculture as production and marketing systems transition towards more demand-driven business models for social inclusivity.